Impact of coronary calcium score on the prevalence of coronary artery stenosis on dual source CT coronary angiography in Caucasian patients with an intermediate risk - Meyer, Mathias; Henzler, Thomas; Fink, Christian; Apfaltrer, Paul; Schönberg, Stefan; Wasser, Klaus (Academic radiology, 2012)
Purpose: To investigate the prevalence of significant coronary artery stenosis on coronary computed tomography angiography (cCTA) in symptomatic Caucasian patients with an intermediate risk score at different levels of coronary artery calcification (CAC). Method: In total, 383 consecutive symptomatic Caucasian patients (147 females, 60 ± 13 years) with an intermediate risk score underwent nonenhanced CT for CAC scoring immediately before contrast-enhanced cCTA on a dual-source CT scanner. Additionally clinically indicated invasive coronary angiography (ICA) was performed in 90 patients. The prevalence of significant coronary artery stenosis (>50%) on cCTA and ICA was correlated at different CAC score levels. Results: Of 121 patients with a zero CAC score, none had significant coronary artery stenosis on cCTA or ICA. Coronary CTA diagnosed in 54 of 70 patients with high CAC score (>400), a significant stenosis. Subsequent ICA confirmed significant stenosis in 30 of 32 patients. Sensitivity and a negative predictive value of CAC score ruling out significant stenosis on cCTA were 100% and 100%, respectively, using cutoff value of zero and specificity and positive predictive value to predict significant stenosis on cCTA were 79% and 51%, respectively, using a cutoff value of >400. Conclusion: Significant coronary artery stenosis is extremely unlikely, with an estimated risk of 4 in 1000 patients in symptomatic Caucasian patients with an intermediate risk score and negative CAC score. To reduce radiation exposure, radiation-free tests should be considered for differential diagnosis of chest pain in these patients.
Gesehen am 29.11.2018